The cinematography of Paper Planes, Don't Always Soar - Kiew, Kester (Nanyang Technological University, 2023)
"The Cinematography of Paper Planes, Don't Always Soar" is a documentation of the process in making the thesis film “Paper Planes, Don’t Always Soar.” This report presents a chronological and systematic order, taking the film from pre-production till final delivery.